Pelatihan Pemberdayaan Masyarakat Kreatif Melalui media Tepat Guna Tanaman Hias dengan Teknik Kokedama - K, Hermanu; Nugroho, Sasongko Priyo (STAI Miftahul ULa Nganjuk, 2019)
The purpose of community assistance at Sunan Giri University Surabaya through training and empowerment of the creative economy through ornamental garden cultivation with the Kokedama Technique. Pendekatan uses community parchiveatories to carry out training on ornamental planting cultivation with kokadame techniques in collaboration with experts and experts from the park's Landscape design service. The results of the assistance show that the assisted community has the ability independently to produce a variety of ornamental plants that can be marketed through online or mini storefronts of ornamental plants in front of residents' homes or agencies and certain spots in Janti village.